2018
DOI: 10.1002/joc.5782
|View full text |Cite
|
Sign up to set email alerts
|

Is there a quiescent typhoon season over the western North Pacific following a strong El Niño event?

Abstract: Previous studies found that tropical cyclone (TC) formation is generally suppressed over the western North Pacific (WNP) following strong El Niño events. The 2015/2016 event is identified as one of the three major El Niño events since 1950. However, a climatological average of 26 named TCs occurred over the WNP in 2016. The plausible causes for this inconsistency are investigated in this study. By examining the historical records, we also found that 28 named TCs occurred over the WNP following 1991/1992 El Niñ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Maue () suggested that NH TC activity is closely linked to the dominant modes of NP climate variability such as the North Pacific Gyre Oscillation (NPGO). A negative phase of the NPGO occurred in the summer of 2018, which seems to be consistent with the heightened TC activity that the NH experienced in 2018 (Maue, ; C. Wang et al, ; Wei Zhang et al, ). But it is unclear how abnormal the year 2018 is compared to historical records.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Maue () suggested that NH TC activity is closely linked to the dominant modes of NP climate variability such as the North Pacific Gyre Oscillation (NPGO). A negative phase of the NPGO occurred in the summer of 2018, which seems to be consistent with the heightened TC activity that the NH experienced in 2018 (Maue, ; C. Wang et al, ; Wei Zhang et al, ). But it is unclear how abnormal the year 2018 is compared to historical records.…”
Section: Introductionsupporting
confidence: 63%
“…In fact, the temporal evolution of subtropical NP SST was significantly correlated with that of the Pacific Meridional Mode (PMM, Chiang & Vimont, ) index with a correlation coefficient of 0.78 over 1965‐2018. This close connection suggested their similar effects on TC activity in the WNP (C. Wang, Wu, et al, ; Y.‐K. Wu et al, ; Zhan et al, ; W Zhang et al, ) and the ENP (Collins et al, ; Murakami et al, ; Wood et al, ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In recent decades, the TC activity over the WNP basin has demonstrated significant changes (Wu and Wang, ; Yu et al ., ; Wang and Wu, ; Wang et al ., ). The 24 hr TC track forecasts from the National Meteorological Center of the China Meteorological Administration have significantly improved, but there is still much room for improvement when considering sudden deflection and looping tracks in some special large‐scale environments (Xu et al ., ).…”
Section: Introductionmentioning
confidence: 97%